PENGEMBANGAN SOAL TES BERPIKIR TINGKAT TINGGI MATERI FLUIDA UNTUK SMA - Nova Liana; Wayan Suana; Feriansyah Sesunan; Abdurrahman (JOURNAL OF KOMODO SCIENCE EDUCATION, 2018)
The purpose of this research is to design the two-tier multiple-choice (TTMC) test on fluid material by Rasch Model analysis. Development was adopted from Adams and Wieman (2011) including the format of item and construction of item sets, assessment guidelines assigning, expert test, and a revision of item. The subject of research trials was 57 students of grade XI MIA in SMAN 1 Kotaagung. The data obtained were analyzed using the Rasch Model with Winstep 3,73 applications. Based on the results of research, it was concluded that (1) questions of HOTS developed was valid {achieve the acceptable ranges of PT-Measure, Outfit Mean Square (MNSQ), and value of Outfit z-standardized (ZSTD)}, (2) questions of HOTS developed have excellent reliability with alpha chonbrach’s of 0.94, (3) there are 5 very difficult questions, 10 difficult questions, 11 easy questions, and 4 very easy questions, (4) respondent has good consistency of answer, (5) deception options on all item was valid, and (6) all items have a discrimination very good with value of Pt Measure Corr more than from 0,40. Questions of HOTS that developed can increase the higher-order thinking skills of students so they have a good mastery of a concept.